Les représentations sur la formation à distance - Marc Trestini; Richard Cabassut (Centre National d'Enseignement à Distance, 2019)
The objective of this research is to explore how distance teacher training schemes (EAD, FOAD, MOOC, OER) are designed and implemented through the representations (beliefs) of trainers. We already know that trainers' representations of education in general have a significant influence on the way they organise teacher training in the classroom. Our objective is to observe these teacher trainers' representations of distance learning and to analyse how they influence the way in which the distance learning scenarios are designed and implemented. To capture their representations and shed light on the questioning related to pedagogical engineering, we interviewed them using an online questionnaire and a semi-directive interview lasting approximately one hour. This allowed us to observe similarities and differences in their representations, objectives, pedagogical scenarios and institutions carrying training projects.